2015
DOI: 10.1186/s40064-015-0913-y
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of outcomes for small cell carcinoma of the breast by tumor stage and the use of radiation therapy

Abstract: PurposePrimary small cell carcinomas of the breast (SCCB) are rare tumors with limited data on outcomes and treatment strategies. Using a population based approach, we aimed to study outcomes of SCCB and determine whether the use of radiation therapy is associated with better survival among patients with SCCB.MethodsUsing the Surveillance, Epidemiology and End Results (SEER) registry, we identified patients with SCCB between1973 and 2010. We examined the stage specific survival of these patients and compared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Small cell carcinoma of the breast has been very rarely reported in the literature [ 8 11 ]. The largest population-based series, by Hare et al ., included 199 patients with small cell carcinoma of the breast, who were compared with patients with small cell lung carcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Small cell carcinoma of the breast has been very rarely reported in the literature [ 8 11 ]. The largest population-based series, by Hare et al ., included 199 patients with small cell carcinoma of the breast, who were compared with patients with small cell lung carcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While similar characteristics between small cell carcinoma of the lung and small cell carcinoma of the breast are seen, there may be inherent biologic differences. Options for treatment of small cell carcinoma of the breast include surgery, adjuvant chemotherapy and radiation, and hormonal therapy with the options dependent on the stage and expression of receptors [1,8]. Due to the paucity of data, the optimal management of small cell carcinoma of the breast remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Small cell carcinoma of the breast accounts for 2-5 % of all breast cancer [5]. A population-based study of small cell carcinoma in the United States from 1992 to 2010 showed that extrapulmonary small cell carcinoma is associated with a more favorable stage-specific patient survival [6]; specifically, small cell carcinoma of the breast has a more favorable prognosis for localized and regional disease than small cell carcinoma of the lung [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,17 Adjuvant hormonal therapy is added if the tumor expresses the appropriate receptors. 6,15,17 However, there is no consensus and no trials comparing these 2 chemotherapeutic strategies. Most studies have shown that high-grade neuroendocrine carcinomas of the breast are very aggressive neoplasms, having poorer prognosis than the more common ductal and/or lobular infiltrating carcinomas.…”
Section: Discussionmentioning
confidence: 99%